Kepekaan Cacing Laut Ophryotrocha diadema (Polychaeta: Dorvilleidae) terhadap Cemaran Metil Merkuri (MeHg) - Markus Talintukan Lasut; Henneke Pangkey (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Susceptibility of the marine polychaete Ophryotrocha diadema (Polychaeta: Dorvilleidae) towards the neurotoxic methyl mercury (MeHg) contamination was studied in an experimental chamber, which was aimed to assess and compare the susceptibility level of the organism based on its generations (F0, F1, F2, and F3). Seven variables of growth and reproduction aspects were applied as indicators in this study; they were: 1) individual growth, 2) first time the egg laid, 3) number of eggs per individu, 4) number of eggs per egg mass, 5) number of eggs to larva per egg mass, 6) number of mortality per egg mass, and 7) reproductive potential. Observation was conducted on the treatment (MeHg in concentration of 0,00025 ppb) and the control (no MeHg) to each of the generations (F0, F1, F2, and F3). Data obtained were analysed for average and standard deviation. Comparison of susceptibility within the generations was calculated using the variable of reproductive potential. The results showed that there were differences between the treatments and the control for all of the variables. Comparison on the susceptibility of the polychaete within the generations to MeHg contamination was F0<F1=F3<F2. It was concluded that the F2 generation had the highest susceptibility among the others.